VISUAL BRANDING RAJUT LASNA - ICE RAMAYANI, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this design is to design a visual branding of Mrs. Lasnawinda’s knitting business by using ‘lasna’ as a brand identity, which is taken from the owner’s own name. Brand Lasna hopefully will make the consumers can recognize lasna’s products easily from other competitors. This visual branding is designed to help the company introduces Lasna ‘s product to their potential consumers. An appropriate strategy shall be made to express characteristic from Lasna’s Product So that lasna can build consumer awareness and also be able to loyal to the brand. the design stages start with research, data analysis, and design. The research data were done by interviews, observation, and documentation. These data were analyzed by using S.W.O.T analysis.The main media for the visual branding of lasna is a manual book, which is useful as a guide for lasna company to apply the brand so that lasna can always keep consistent with their image and characteristic. Also, promotional media such as stationery set, exhibition poster, X-banner, T-shirt, Paper bag, Tags, and social media pages. Every promotional media has an important role in raising awareness to the consumers.Keywords : knitting, Lasna knitting , Manual book, Brand.